2022
DOI: 10.33448/rsd-v11i10.32624
|View full text |Cite
|
Sign up to set email alerts
|

Medicación antihipertensiva y sus reacciones adversas en la cavidad oral. Una revisión integrativa

Abstract: El uso de la medicación antihipertensiva ha permitido reducir las complicaciones relacionadas con la hipertensión arterial. Sin embargo, el uso de estos fármacos ha generado reacciones adversas en la cavidad bucal como la xerostomía, hiperplasia gingival, alteraciones del gusto, entre otras. El presente estudio tiene como objetivo identificar en la literatura las reacciones adversas o efectos indeseables relacionadas a la terapia antihipertensiva. Se realizó una búsqueda en las bases digitales en PubMed, Scopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…As explained before, there is no significant correlation between hypertension and oral lesions, the coexistence of both conditions is possibly because of medication used in hypertension that causes hyposalivation. 15 19 20 In this study, 125 elderly (85.03%) use amlodipine as their medication. amlodipine is a first-choice antihypertensive drug from the group of calcium channel blockers that has a mechanism of action by inhibiting the influx of calcium ions into heart muscle cells and vascular smooth muscle so that the relaxing effect results in decreasing BP.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…As explained before, there is no significant correlation between hypertension and oral lesions, the coexistence of both conditions is possibly because of medication used in hypertension that causes hyposalivation. 15 19 20 In this study, 125 elderly (85.03%) use amlodipine as their medication. amlodipine is a first-choice antihypertensive drug from the group of calcium channel blockers that has a mechanism of action by inhibiting the influx of calcium ions into heart muscle cells and vascular smooth muscle so that the relaxing effect results in decreasing BP.…”
Section: Discussionmentioning
confidence: 87%
“…14 Current studies state that there is no recognized oral manifestation of hypertension but medication using antihypertensive drugs can often develop side effects in the oral cavity. 15 This study focuses on normal variant lesions on the tongue because the previous study showed that the tongue is a good indicator of the oral cavity as a mirror of general health and easy accessibility in daily examination. 16 The result of this study showed that fissured tongue is the most common normal variant lesions on the tongue found in the elderly with hypertension (n ¼ 133; 90.48%).…”
Section: Discussionmentioning
confidence: 99%
“…Ayinampudi et al [22] Hemodialyzed non-diabetic patients (11) Candida observed in 3 samples (27%) The high-risk ratio (1.774) is an indication that the presence of Candida is probably higher in diabetic patients.…”
Section: Reference Group (N) Results Conclusionmentioning
confidence: 99%
“…Medications used in the treatment of hypertension may lead to gingival overgrowth, xerostomia, salivary gland swelling, lichenoid reactions, taste disorders, and parathesis [10]. Most side effects are observed in therapy with the following group of medications: angiotensin-converting enzyme inhibitors, calcium channel blockers, and diuretics [11].…”
Section: Introductionmentioning
confidence: 99%
“…The long-term use of anti-hypertension medications results further in xerostomia [159]. Dry mouth then raises caries prevalence in the mouth of the users.…”
Section: Anti-hypertensivesmentioning
confidence: 99%